Employing Of the Television the Technologies in Production the News Bulletins - Wria Rostam Muhamad; Radwan Khidhir Ali; Hakim Othman Hameed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims to identify the most important modern technologies used and the extent to which they are employed in presenting and presenting news bulletins in the “Rudaw” satellite channel, and in order to achieve this, a regular random sample was selected from all bulletins (at eight o’clock in the evening - health - sports) and throughout the program cycle of the channel. For a period of (six months) starting from 1-1- 2021 to 30-6- 2021, in which the researcher relied on taking an industrial month of (30) days representing the target community consisting of (90) (bulletins). This study belongs to the descriptive studies that relied on the sample survey method, through the two tools of observation and survey content analysis of all data from the study sample. The study reached a number of results, the most important of which are: There is a diversity in the methods of presenting news in news bulletins on Rudaw satellite channel, and the method of “the announcer gives an idea of ​​the news in addition to showing motion graphics and infographics” was more used in presenting news bulletins, and the “announcer with the reporter” method was less used. And that Rudaw satellite channel focused in its presentation of news bulletins on some modern graphic techniques and dispensed with other techniques, and the channel had relied heavily on employing “On Air Graphic- Video Wall- Motion Graphics” techniques, while other techniques were not employed, the most important of which is Virtual studio and hologram technology in any way, while 3D technology is used very little.